Nutritional conditions indicators in Poionoroeste Area: VI - Anthropometric study, 1985 - Spinelli, M.A. dos Santos; da Silva, R.R.; Albuquerque, M.C.W.; Yokoo, E.M.; Guimarães, L.V. (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
The presence of DPC (Caloric, Proteic Undernutrition) has been expressive in the country showing social and economic differences of the distinct regions. As part of the Health Diagnostic Survey in Poionoroeste in 1985, has been done an anthropometric study of weight and height out of a sample of 405 children under 6 years of age in Caceres/MT. In accordance with GOMEZ criteria, the undernutrition prevalence was of 33%, 40% of moderated underfed and no one case of a serious undernutrition was observed. The WATERLOW's classification showed the past undernutrition (36%) has been of more prevalence, being that the more accentuated height defficiencies were under two years of age, indicating that the health programs towards the children in this area, should give priority to the nutritional aspects for this age group.